Establishing Teachers’ Professional Development Through Peer Review - Gendroyono Gendroyono (Publikasi Indonesia, 2021)
The demand for professional development for teachers in higher education is paramount. In doing so, the teachers must have a good professional development scheme in upgrading their knowledge and skills in performing their main duty. This research was aimed at investigating the areas of teachers’ professional development which are supported by the implementation of peer review in team teaching. It also aims at exploring the challenges in applying team teaching. This study applied qualitative research design with the interview as the data collection method and four English teachers as the participants of the research. The result showed that there are three aspects of TPD which occur. The first one is an attitude which becomes better in terms of improved awareness of the teachers. The other element is self-esteem where it is also improved due to the feedback given after the peer review. While the third is patience. As suggested in the feedbacks, teachers require to be more patients in dealing with misbehaving students. As for the challenges, it can be concluded that they come from two different sources. The first one is from the individual teacher where they think that some of the suggestions cannot be done or too hard to do. The second one is, Since TPD requires funding, the institution should also provide necessary and sufficient funding to support the TPD. This can be done by setting up the policy dealing with the sustainable TPD which, in turn, will give more benefits to the institution.